Peran dan Posisi Asuransi Syariah di Indonesia - Anwar, Syahrul; Suryani, Eli; Qiftia, Maryathul; Sephia, Reyhan (LPPM Universitas Islam 45, 2025)
The purpose of the article is to analyze the definition and role of Islamic insurance in maintaining human welfare and strengthening economic growth. This research uses a type of qualitative research with the approach method used by researchers is a library study approach (Library Research). Data collection uses literature studies such as books, scientific journals and written reports related to Islamic insurance and economic growth. The results of this study indicate that there are various definitions of Islamic insurance and Islamic insurance plays an important role for human benefit and strengthens economic growth. Islamic insurance also plays an important role in maintaining the five elements that are the foundation of human welfare, namely protecting religion, soul, mind, offspring and property or known as (Maqashid Syariah). Islamic insurance plays an important role in increasing investment, improving the community's economy, as a source of development financing, and can sharing financial risks caused by unexpected events or disasters